Studi Kasus Tentang Kesulitan Siswa dalam Menentukan Gagasan Pokok Paragraf Kelas IV UPT SD NEGERI 90 Sampulungan - Anisa Almaimuna; Kasrawi; Abdul Azis; Kasriany (PT. Saha Kreasi Indonesia, 2025)
This study aims to describe the difficulties experienced by fourth-grade students at UPT SD Negeri 90 Sampulungan in identifying the main idea of a paragraph. The research subjects consisted of 28 students, including 11 boys and 17 girls. This study employed a descriptive qualitative method with data collected through observation, tests, and interviews. The findings reveal that most students still struggle to identify the main idea, particularly in distinguishing main sentences from supporting details, limited vocabulary mastery, and a tendency to guess the main idea without comprehensively understanding the text. These challenges contribute to low learning outcomes, with only a small number of students able to correctly determine the main idea. The discussion highlights that both internal factors (reading comprehension ability, vocabulary, and concentration) and external factors (instructional strategies and limited learning media) contribute to students’ difficulties. Therefore, innovative teaching strategies, diverse learning media, and strengthened learning motivation are needed to optimally improve students’ reading literacy skills.